Air Quality Visualization in Valencia: An Interactive Tool for Citize - Coma Tatay, Inmaculada; Domenech, Francesc; Carot, Vicente; Portalés Ricart, Cristina (Observatorio Medioambiental, 2025)
Air quality is a key indicator of environmental health, and its effective communication is essential to support informed decision-making. In Valencia, although official air pollution data are openly available, their complexity hinders public understanding. This paper presents a web application that integrates real-time and historical information from eleven monitoring stations, enabling interactive visualization of the main pollutants (NO₂, PM₁₀, PM₂.₅, O₃, SO₂) together with reference values from Spanish legislation and WHO guidelines. The tool combines maps, temporal charts, and heatmaps to facilitate trend analysis, comparison with regulatory thresholds, and identification of critical periods. Results reveal a progressive decline in NO₂ and PM₁₀ levels between 2014 and 2023, as well as seasonal patterns linked to ozone. The proposed platform helps democratize access to environmental information, raise public awareness, and provides a replicable resource for other cities seeking to make air-quality data more accessible to citizens